2013
DOI: 10.1038/ncomms3474
|View full text |Cite
|
Sign up to set email alerts
|

Human impacts drive a global topographic signature in tree cover

Abstract: The Anthropocene is a geological epoch marked by major human influences on processes in the atmosphere, biosphere, hydrosphere and geosphere. One of the most dramatic features of the Anthropocene is the massive alteration of the Earth's vegetation, including forests. Here we investigate the role of topography in shaping human impacts on tree cover from local to global scales. We show that human impacts have resulted in a global tendency for tree cover to be constrained to sloped terrain and losses to be concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 35 publications
6
71
0
Order By: Relevance
“…Li et al (2002) provide evidence that Rhinopithecus was first extirpated from lower elevation during the last 400 years. Higher elevation areas are more remote and difficult for humans to access and utilize and other studies have found less deforestation, more reforestation and afforestation, less range contraction, and less extinction in topographically steep areas (Laliberte and Ripple 2004; Fisher 2011; Sandel and Svenning 2013; Faurby and Svenning 2015; Nüchel and Svenning 2017). Furthermore, many other species in the region, e.g., giant panda ( Ailuropoda melanoleuca ) and red panda ( Ailurus fulgens ), have also been impacted by strong anthropogenic pressure during the recent centuries with population declines and range retractions as consequences (Ceballos and Ehrlich 2002; Zhu et al 2010; Hu et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Li et al (2002) provide evidence that Rhinopithecus was first extirpated from lower elevation during the last 400 years. Higher elevation areas are more remote and difficult for humans to access and utilize and other studies have found less deforestation, more reforestation and afforestation, less range contraction, and less extinction in topographically steep areas (Laliberte and Ripple 2004; Fisher 2011; Sandel and Svenning 2013; Faurby and Svenning 2015; Nüchel and Svenning 2017). Furthermore, many other species in the region, e.g., giant panda ( Ailuropoda melanoleuca ) and red panda ( Ailurus fulgens ), have also been impacted by strong anthropogenic pressure during the recent centuries with population declines and range retractions as consequences (Ceballos and Ehrlich 2002; Zhu et al 2010; Hu et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Although our study focused on forests in absence of topography, we believe the mechanisms behind cloud cover enhancement will also play a role in the presence of a static lifting mechanism. However, as forest cover correlates spatially with topography26, disentangling these effects can no longer be done based on observations alone and will require a systematic modelling approach. Future research will have to learn whether convective cloud preference over forests is also associated with triggering of deep convection and increased rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…This allows a study of regional-scale land-use effects in isolation of confounding orographic effects. Most other large forest regions in Europe are located in hilly or mountainous areas26 where land-use effects cannot be isolated from orographic effects based on observations alone. The forest size (Landes has a forest area of over 12,000 km 2 ) is also large enough for ABL conditions to reflect forest surface conditions.…”
mentioning
confidence: 99%
“…Alas, this is less due to the recognition of mountains as important centres of diversity, and rather to the historical difficulties in using steep slopes for timber extraction, agriculture or urbanization. The biodiversity of these same areas has been disproportionally spared from human influence for many of the same reasons (Sandel & Svenning, ). Other non‐biological reasons for mountain protection include scenic qualities and their role in water provision (Hamilton & McMillan, ).…”
Section: Why Are There So Many Species On Mountains?mentioning
confidence: 99%